MULTISERVICE NETWORK SERVICES - Olimov Olimboy (Web of Journals Publishing, 2024)
This article provides information about the type of information transmitted in multimedia communications networks, the type of service in the exchange of information, the methods of classifying the client's connection and services to the client, Types of services and their implementation. About the quality of telecommunication services. Service agreement. Management of the level of service and monitoring of its implementation.
Keywords: RSVP, Intserv, DiffServ, frame, Jitter, traffic, header.